Sea urchin grazing preferences on native and non-native macroalgae. (April 2020) - Cardoso, André C.; Arenas, Francisco; Sousa-Pinto, Isabel; Barreiro, Aldo; Franco, João N.
Highlights: Herbivory by the sea urchin P. lividus revealed no preference amongst native and non-native algae. P. lividus did not show feeding preference neither in the brown or the red tested seaweeds. Brown and red seaweeds phenolic and nutritional contents did not drive P. lividus food preferences. Abstract: Herbivory plays a major role in shaping community dynamics across freshwater, marine and terrestrial habitats, by controlling patterns of abundance and distribution of primary producers, including seaweeds. In the context of biological invasions, the proliferation of non-native seaweeds has been often attributed to limited grazing by native herbivores on introduced species ("Enemy Release Hypothesis", ERH). In our study, we aimed to explore the potential of an abundant generalist herbivore (the sea urchin Paracentrotus lividus ) to graze on non-native in comparison to native macroalgae species. For this purpose, we used manipulative experiments to assess sea urchin preference on native and non-native seaweed species present in the northwest coast of Portugal. Specifically, we determined the preferences of P. lividus on brown seaweeds i.e. Laminaria ochroleuca, Saccorhiza polyschides and the non-native Undaria pinnatifida, and red seaweeds i.e. Chondrus crispus, Mastocarpus stellatus and the non-native Grateloupia turuturu . For each group of seaweed species, sea urchin preference and biomass consumption were examined. The nutritional (organic carbon and nitrogen) and chemical (phenolic content) features were also analysed, in order to assess their effect on sea urchin feeding. According to the results, P. lividus did not show a specific preference for any of the different seaweeds of each phylum. These results suggest that P. lividus is a generalist herbivore, not exerting a differential grazing pressure on non-native seaweeds when compared to native ones.